THE FIRST AORTIC STENT-GRAFT PLACEMENT IN THAILAND - TAPANEEYAKORN, Jiemjit; LEELAUDOMLIPI, Surasak; SRIPHOJANART, Suthus; BOONBAICHAIYAPRUCK, Sarana; SIRIPORNPITAK, Suvipaporn (The ASEAN Journal of Radiology, 2023)
The first patient in Thailand, a 67 years-old female having liver cirrhosis with an asymptomatic huge infra-renal aortic aneurysm, who has an aortic stent graft, was reported.